Distribution and Genetic Variability of Fusarium oxysporum Associated with Tomato Diseases in Algeria and a Biocontrol Strategy with Indigenous Trichoderma spp. - Debbi, Ali; Boureghda, Houda; Monte, Enrique; Hermosa, Rosa (Frontiers in Microbiology, 2018)
Fifty fungal isolates were sampled from diseased tomato plants as result of a survey conducted in seven tomato crop areas in Algeria from 2012 to 2015. Morphological criteria and PCR-based identification, using the primers PF02 and PF03, assigned 29 out of 50 isolates to Fusarium oxysporum (Fo). The banding patterns amplified for genes SIX1, SIX3 and SIX4 served to identify races 2 and 3 of Fo f. sp. lycopersici (FOL), and Fo f. sp. radicis lycopersici (FORL) among the Algerian isolates. All FOL isolates showed pathogenicity on the susceptible tomato cv. “Super Marmande,” while nine of out 10 Algerian FORL isolates were pathogenic on tomato cv. “Rio Grande.” Inter simple sequence repeat (ISSR) fingerprints showed high genetic diversity among Algerian Fo isolates. Seventeen Algerian Trichoderma isolates were also obtained and assigned to the species T. asperellum (12 isolates), T. harzianum (four isolates) and T. ghanense (one isolate) based on ITS and tef1α gene sequences. Different in vitro tests identified the antagonistic potential of native Trichoderma isolates against FORL and FOL. Greenhouse biocontrol assays performed on “SM” tomato plants with T. ghanense T8 and T. asperellum T9 and T17, and three Fo isolates showed that isolate T8 performed well against FORL and FOL. This finding was based on an incidence reduction of crown and root rot and Fusarium wilt diseases by 53.1 and 48.3%, respectively.